The Economics of Identity: How EDI Initiatives Treat Racialized Identities as Currency in Academic Libraries - Liu, Tina (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2024)
This paper examines and critiques top-down institutional EDI policies and plans from Canadian academic libraries. Using David James Hudson’s critique of how the diversity model overemphasizes representation over meaningful action, this paper explores how the EDI plans and policies at Canadian academic libraries facilitate the exchange of racial capital, thereby reducing racialized identities to currency. To explore pathways forward, I conducted a thematic analysis of EDI plans and policies from all Canadian academic libraries. This thematic analysis informs strategies for how people within Canadian academic institutions can move beyond the diversity model to recentre meaningful and effective equity work. The paper closes with a call towards embedded EDI practices informed by Indigenous concepts of decolonial indigenization and relationality.